PENGARUH PRE OPERATING TEACHING (INFORM CONSENT) TERHADAP PENURUNAN TINGKAT KECEMASAN PADA PASIEN PRE OPERATIF SECTIO CESARIA DI RUMAH SAKIT X DENPASAR - Iyut Putu Dessy Guritnawati; I Nyoman Sutresna; A.A Kompiang Ngurah Darmawan (Journal of Advanced Nursing and Health Sciences, 2021)
Inadequate health information can increase anxious reactions in patients and their families so that the preoperative information for cesarean section (informed consent) provided by officers aims to straighten out the patient's inaccurate perception or understanding of surgery. This study aims to see "the effect of pre operating teaching (inform consent) on decreasing levels of preoperative section cesarean patients at X Hospital Denpasar. This study used a comparative descriptive method with pre-test and post-test designs. The sampling method in this study using accidental sampling method with a total sample of 32 respondents. Data analysis was tested by Wilcoxon Rank Sum Test with significance p <0.05. The results of the study obtained a data value of 0,000, where the p-value (0,000) was smaller than the determined significant level (p <0.05) so that it can be ignored that the hypothesis of this study was accepted, namely that there was an effect of pre-operation teaching (inform consent) on reduction in the rate of reduction in preoperative section caesarean patients at X Hospital